2013
DOI: 10.1007/s12469-013-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in bus transit service: understanding the impacts of various improvement strategies on transit service reliability

Abstract: Transit agencies wishing to offer reliable service with less variability compared to schedules face several challenges, encouraging them to employ various strategies. While previous research has considered the effects of various strategies on running time, there has been little effort to understand their impacts on reliability of service. This article examines the impacts of various improvement strategies, implemented by Société de Transport de Montréal (STM) along one of its heavily utilized bus routes, on ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…For 57 example, Schwartz et al (1982) found that during peak-hour, bus speed increased by 83% and 58 bus reliability increased by 57 percent while traffic speed on the relevant street increased by 10 59 percent. In contrast, Diab and El-Geneidy (2013) found that while the operation of an exclusive 60 bus lane had a modest effect on reducing bus running time by 2.7%, travel time variability 61 increased by 0.5% due to the effect of right turning vehicles. Their study analysed empirically a 62 mix of measures to improve transit performance in Montreal using automated vehicle location 63 (AVL) and automated passenger counts (APC) data with a focus on reliability.…”
Section: Introduction 26mentioning
confidence: 83%
“…For 57 example, Schwartz et al (1982) found that during peak-hour, bus speed increased by 83% and 58 bus reliability increased by 57 percent while traffic speed on the relevant street increased by 10 59 percent. In contrast, Diab and El-Geneidy (2013) found that while the operation of an exclusive 60 bus lane had a modest effect on reducing bus running time by 2.7%, travel time variability 61 increased by 0.5% due to the effect of right turning vehicles. Their study analysed empirically a 62 mix of measures to improve transit performance in Montreal using automated vehicle location 63 (AVL) and automated passenger counts (APC) data with a focus on reliability.…”
Section: Introduction 26mentioning
confidence: 83%
“…Strategy assessment (operators) 4.6.1 Diab and El-Geneidy (2013) studied the impacts of various improvement strategies on service reliability and concluded that the strategies can decrease the standard deviation of travel time. Assuming the current service travel time distribution follows a 3-components GMM model (GMM3), the parameters for the GMM3 model are set as …”
Section: Discussion and Applicationsmentioning
confidence: 99%
“…These strategies include smart fare card collection system, reserved bus lanes, limited-stop bus services, stop consolidation, articulated buses and transit signal priority. Diab and El-Geneidy (2013) further investigated the impact of the implementation of various strategies on service variations.…”
Section: Travel Time Reliability Modelling 233mentioning
confidence: 99%
See 2 more Smart Citations